Large eddy simulation of lean turbulent hydrogen-enriched methane-air premixed flames at high Karlovitz numbers. (21st December 2016) - Cicoria, David; Chan, C.K.
Abstract: Large eddy simulation (LES) is employed to investigate the effects of hydrogen within the fuel mixture for lean CH4 –H2 turbulent premixed flames in the distributed reaction zone (high Karlovitz number). The subfilter combustion term representing the interaction between turbulence and chemistry is modelled using the partially stirred reactor (PaSR) model, along with complex chemistry using a skeletal mechanism based on the GRI-MECH3.0, to handle mixtures up to 60% of hydrogen in volume. The influence of hydrogen enrichment at high turbulence levels is studied by means of the local flame structure, and the assessment of species formation inside the flame. Results show that with higher hydrogen content, the flame displays a higher degree of wrinkling and is shorter because of a higher turbulent flame speed. The local structure of the flame is mainly affected by the turbulence but differential diffusion effects still play a role in the flame front aspect, especially when hydrogen addition becomes important. Concerning the formation of intermediate species and pollutants, by increasing the amount of hydrogen in the fuel mixture at fixed equivalence ratio, more emissions are reported. This is expected as the mixture reactivity (heat release) increases when substituting methane by hydrogen in the unburned mixture. Highlights: Effects of hydrogen addition in highly turbulent methane-air flames. LES is used with finite rate chemistry procedure. Ability to capture flame features of hydrogen-enriched premixed flames. Preferential diffusion remains important at high turbulence levels. Intermediates species and NO are formed in higher amount with hydrogen enrichment.